2009
DOI: 10.4049/jimmunol.0802722
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IDO by Bacille Calmette-Guérin Is Responsible for Development of Murine Depressive-Like Behavior

Abstract: Chronic inflammation activates the tryptophan-degrading enzyme IDO, which is well known to impair T cell proliferation. We have previously established that bacille Calmette-Guérin (BCG), an attenuated form of Mycobacterium bovis, is associated with persistent activation of IDO in the brain and chronic depressive-like behavior, but a causative role has not been established. In these experiments we used both pharmacologic and genetic approaches to test the hypothesis that IDO activation is responsible for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
278
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(299 citation statements)
references
References 78 publications
12
278
0
8
Order By: Relevance
“…Laboratory animal studies have provided a rich array of experiments that demonstrate the role of IDO and its activation of the kynurenine pathway (KP) in the development of depressive symptoms in the context of a variety of immune stimuli. Studies in mice exposed to LPS as well as Bacille CalmetteGuerin (BCG) have demonstrated that inhibition of IDO by 1 methyltryptophan (1 MT) completely reversed increases in the kynurenine/tryptophan ratio and reversed depressiveand anxiety-like behaviors including sucrose preference, whereas it had no effect on inflammatory markers in the brain (O'Connor et al, 2009;Salazar et al, 2012). Although much attention has been paid to the two primary pathways downstream of IDO leading to quinolinic acid (the 'neurotoxic pathway') and kynurenic acid (the 'neuroprotective pathway'), data suggest that this distinction may be too simplistic, and it is very apparent that both pathways can contribute to pathology.…”
Section: Reviewmentioning
confidence: 99%
“…Laboratory animal studies have provided a rich array of experiments that demonstrate the role of IDO and its activation of the kynurenine pathway (KP) in the development of depressive symptoms in the context of a variety of immune stimuli. Studies in mice exposed to LPS as well as Bacille CalmetteGuerin (BCG) have demonstrated that inhibition of IDO by 1 methyltryptophan (1 MT) completely reversed increases in the kynurenine/tryptophan ratio and reversed depressiveand anxiety-like behaviors including sucrose preference, whereas it had no effect on inflammatory markers in the brain (O'Connor et al, 2009;Salazar et al, 2012). Although much attention has been paid to the two primary pathways downstream of IDO leading to quinolinic acid (the 'neurotoxic pathway') and kynurenic acid (the 'neuroprotective pathway'), data suggest that this distinction may be too simplistic, and it is very apparent that both pathways can contribute to pathology.…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, our simulations predict that the ratio of mean fluxes through KAT/KMO decreased by 28.1% in T. meningitis patients. O'Connor et al (41) showed that induction of IDO by Bacille Calmette-Guerin (a pathogen widely used as a vaccine against tuberculosis) is responsible for a depressive-like behavior in mice. They proposed that a shift to a less favorable ratio of neuroprotective and neurotoxic kynurenine derivatives could contribute to a depressive phenotype.…”
Section: Metabolitementioning
confidence: 99%
“…Several investigations have focused on potential mechanisms linking inflammation-induced depression to tryptophan metabolism, as a reduction in the bioavailability of tryptophan could affect serotoninergic neurotransmission in the brain, leading to depressive symptoms [28,29]. Those studies have shown that the proinflammatory cytokines interleukin (IL)-1β, tumour necrosis factor (TNF)-α and interferon (IFN)-γ, and lipopolysaccharide (LPS), are capable of activating the enzyme indoleamine 2, 3-dioxygenase (IDO) [30][31][32], a tryptophan-degrading enzyme that oxidizes tryptophan to n-formylkynurenine. A hallmark of HIV infection is the presence of abnormal levels of immune activation and inflammation with high concentrations of proinflammatory cytokines, and high plasma LPS levels [33].…”
Section: Depression In Hiv-infected Patients 217mentioning
confidence: 99%